Ekstraksi Kayu Artocarpus lakoocha: Pengaruh Metode Dan Rasio Bahan Tumbuhan-Penyari Terhadap Rendemen Ekstraksi - Dwi Hartanti; Jirapat Theeravit (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2018)
Artocarpus lakoocha Roxb. (Ma-haad) is a medicinal plant commonly used in Thai Traditional Medicine (TTM) for a wide array of indications. In this study, we compared yield of extraction and the Thin Layer Chromatography (TLC) profile of the heartwood of A. lakoocha extracted with the different methods and different material-solvent ratios. Extractions were carried out by maceration and reflux extraction with ethanol as the solvent, in material-solvent ratio of 1:5 and 1:3. The TLC profile was obtained from the separation of the extracts with methylene chloride/methanol (85:15) on silica gel F254 plate. The result exhibited that reflux extraction produced the highest yield of extraction and the material-solvent ratio of 1:3 generated more yield than that of 1:5. Nevertheless, the profile of TLC chromatogram of those extracts were similar.